in vitro: Production of Pyrogenic Substances in the Reaction of Cells of Hyper-sensitive Guinea Pigs with Antigen - Johanovský, J. (1960)
Previous findings of the appearance of pyrogenic activity when spleen and lymph node cells from BCG-sensitized rabbits were incubated with tuberculin in vitro have been repeated and extended in experiments with guinea pigs. Two different systems were used: hypersensitivity induced by BCG infection and by means of diphtheria toxoid-antitoxin precipitates. Cells were incubated in vitro with diluted tuberculin, diphtheria toxoid or Hanks's solution. Supernatant fluids obtained after various incubation periods were tested in normal guinea pigs for their pyrogenic activity and for ability to induce skin inflammatory reactions. Pyrogenic substances were obtained in most of the experiments in which cells of hypersensitive animals were incubated with the specific antigen; experiments with the unrelated antigen and controls were negative. Formation of skin-irritating substances was less regular, and they were sometimes formed non-specifically in control experiments also; in general, however, the results of these experiments agreed with the results of the fever reaction. The results obtained are discussed in relation to the mechanism of delayed hypersensitivity.